The state of hemostasis in pregnant women with hydramnion - Lyoshenko, I. A.; Tarabrin, O. A.; Kirpichnikova, K. P.; Sukhanov, A. A. (Journal of Education, Health and Sport, 2016)
Lyoshenko I. A., Tarabrin O. A., Kirpichnikova K. P., Sukhanov A. A. The state of hemostasis in pregnant women with hydramnion. Journal of Education, Health and Sport. 2016;6(5):149-156. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.51381 http://ojs.ukw.edu.pl/index.php/johs/article/view/3517 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.04.2016. Revised 29.04.2016. Accepted: 12.05.2016. UDC: 616-00 5.1: 616-006.6 The state of hemostasis in pregnant women with hydramnion I. A. Lyoshenko, O. A. Tarabrin, K. P. Kirpichnikova, A. A. Sukhanov Odessa National Medical University, Odessa, Ukraine Authors: Lyoshenko Irina Anatoliyivna - maternity home №2 Odessa, anaesthesiologist, t. 0679378848, e-mail: irenodessa5555@gmail.com Tarabrin Oleg Oleksandrovych - MD, prof., Head of the department of anaesthesiology and Intensive care of ONMedU, Odessa Regional Clinical Hospital, t. 7500372 Kirpichnikova Katerina Petrovna, Ph. D., Department of anaesthesiology and Intensive care of ONMedU Sukhanov Aleksey Aleksandrovich, Ph. D., Department of anaesthesiology and Intensive care of ONMedU Abstract Purpose. To determine the state of various stages of hemostasis in pregnant women with hydramnion as a risk factor for premature detachment of the placenta. Results. There was investigated the state of hemostasis in pregnant women with hydramnion by low piezoelectric thromboelastography (LPTEG) and standard coagulogram. According to the LPTEG results this group of women was found to have increased plasma coagulation potential manifested in elevated constant thrombin activity (TAC) by 76.8%, the intensity of coagulation drive (ICD) by 74.9%, maximum clot density (MA) by 16.8%, shortening of coagulation time (T3) by 7.8% and inhibition of fibrinolysis manifested by decrease in retraction intensity and clot lysis (RICL) by 67.7% (p<0.05). Conclusions. The state of hemostasis in pregnant women with hydramnion is characterized by increased plasma coagulation and inhibition of fibrinolysis potential that are factors of preparing the woman’s body for the upcoming birth to control and minimize blood loss. Keywords: pregnancy, hydramnion, hemostasis, thromboelastography.